The complete mitogenome of clam Corbicula fluminea determined usingnext-generation and PacBio sequencing. Issue 1 (2nd January 2019) - Zhang, Tongqing; Yin, Jiawen; Tang, Shengkai; Li, Daming; Liu, Xiaowei; Gu, Xiankun; Liu, Yanshan
Abstract: Corbicula fluminea is an important aquatic commercial species in China. In this study, we present the complete mitogenome and a phylogenetic analysis of C. fluminea, determined using next-generation and PacBio long read sequencing. The mitogenome of C. fluminea is 17, 423 bp in size, including 13 protein-coding genes, two ribosomal RNA genes, 22 tRNA genes, and a putative control region, all located on the same strand. The base composition of the entire mitogenome showed a conspicuous A + T bias of 70.5 %. The entire mitogenome data produced in this study provides the genomic resources available for future evolutionary studies.